The Socio-cultural Context of Barriers to Exclusive Breastfeeding Practices among Mothers in Karanganyar District Central Java Province - Rahadian, Angga Sisca; Astuti, Yuly (Universitas Airlangga, 2023)
Background: Exclusive breastfeeding has an important role in preventing stunting among children due to chronic malnutrition. According to Indonesia Health Profile 2020, approximately 33.9% of children under six months were not exclusively breastfed. One of the challenges to achieving successful exclusive breastfeeding comes from socio-cultural aspects. Method: This mixed-methods study examined the socio-cultural context of barriers to exclusive breastfeeding among mothers. For a cross-sectional study in Karanganyar District, Central Java Province, a total of 706 participating mothers with children aged between 6–59 months were interviewed using a structured questionnaire in 2021. In addition, in-depth interviews with mothers were conducted to enrich the findings related to the obstacles in giving exclusive breastfeeding. Result: The binary logistic regression found that male children (AOR= 1.64, 95%CI (1.06, 2.56), children living in low-income households (AOR= 2.48, 1.25, 4.92), children with low-educated mothers (AOR= 8.84, 95%CI (3.83, 20.36), children with working mothers (AOR= 6.45, 95%CI (3.79, 10.98), children with pre lacteal feeding (AOR= 5.67, 95%CI (2.33, 13.75) were more likely to have nonexclusive breastfeeding. This study also revealed that 36,1% of mothers in Karanganyar District gave honey as pre-lacteal feeding to the newborn, which hindered exclusive breastfeeding practices. The qualitative approach also confirms this finding. Conclusion: Therefore, it is important to strengthen health promotion programs related to exclusive breastfeeding to mothers and the family through the life cycle approach based on the local context.